White matter microstructural damage and its effect on cognitive impairment in patients with metabolic syndrome and cerebral small vessel disease - Liu, Han; Feng, He; Tian, Bo; Wang, Kaigui; Chen, Yali; Zhou, Xia; Zheng, Wenhui; Zhang, Wei; Xia, Yu; Lv, Daping; Zhu, Xiaoqun; Sun, Zhongwu (Frontiers in Neurology, 2026)
BackgroundMetabolic syndrome (MetS) is linked to cerebral small vessel disease (CSVD) and cognitive impairment in the elderly, but the underlying mechanisms remain unclear. This study investigated whether white matter (WM) microstructural damage mediates the relationship between CSVD severity and cognitive function in patients with MetS.MethodsA total of 170 right-handed participants aged 50–80 years were recruited, including 75 with MetS and 95 healthy controls (HC). MetS participants were divided into MetS without CSVD (MetS-NCSVD, n = 22) and MetS with CSVD (MetS-CSVD, n = 53). Cognitive function was assessed using Montreal cognitive assessment, Stroop color word test (SCWT), trail making test (TMT) and geriatric depression scale. WM integrity was evaluated using diffusion tensor imaging, including fractional anisotropy (FA) and mean diffusivity (MD). Mediation analysis was performed to examine the role of WM microstructural damage in the relationship between CSVD severity and cognitive impairment.ResultsThe MetS-CSVD group had significantly lower FA and higher MD in core WM fiber tracts compared to MetS-NCSVD and HC groups (P < 0.001). In the MetS group, FA in these tracts were inversely correlated with cognitive test scores (TMT-B and SCWT-C, P < 0.001). Multiple linear regression analyses confirmed these associations (P ≤ 0.045). Mediation analysis revealed that FA values in WM fiber tracts may mediate the relationship between CSVD severity and cognitive function.ConclusionsOur findings suggest that WM microstructural damage may account for the association between CSVD and cognitive impairment, acting as a potential mediator in MetS patients. Future longitudinal studies are needed to validate these findings and explore causal mechanisms.